(untitled) (Global Journal of Science Frontier Research, 2020)
An investigation was done to characterize and classify paddy and associated nonpaddy soils of the Upper Brahmaputra Valley of Assam. In this study, three districts viz., Sivasagar, Jorhat, and Golaghat in the Brahmaputra valley of Assam were selected. These districts are located in the Upper Brahmaputra Valley Zone (UBV) of Assam. Combined, they cover an approximate area of 9021 sq. Km or about 55.7 per cent of UBV. Six soil profiles, three each from mono-cropped paddy and, associated nonpaddy areas were collected from the districts mentioned. These samples were collected Horizon wise from each soil profile. Each soil sample was dried and passed through a 2 mm sieve. The samples from each pedon were evaluated for morphological and Physicochemical characteristics, based on morphological and physicochemical properties. The soils were classified as Aquic Dystric Eutrudepts (P1), Dystric Eutrudepts (NP1, NP2, P3, NP3) and Dystric Fluventic Eutrudepts (P2).